Huge carbuncle of the neck with intracranial extension: a case report - Sedik, Alaa; Rauf, Muhammad Y.; Makhdoom, Mahmood; Abdo, Ihab; Harga, Abdelhamid; Suliman, Amir; Hussein, Abrar; Ali, Hamza; Altwiher, Rasheed; Alrashidi, Abdullah; Alanazi, Wael; Elhoushy, Salwa; et al. (International Surgery Journal, 2018)
A carbuncle is a coalescence of several inflamed follicles into a single inflammatory mass with purulent drainage from multiple sinuses. They can develop in healthy individuals with no predisposing conditions or in immune-compromised ones. Author are presenting a case report of 57 years old Saudi presented with neglected huge carbuncle of the neck that was found complicated with intracranial extension in the posterior cranial fossa. He underwent successful simultaneous excision of the carbuncle and debridement of gross necrotic tissues; together with evacuation of the intracranial abscess. Both general and neurosurgical teams were involved. Patient made uneventful recovery and discharged home in good condition.